# Logistic classification with cross-entropy (1/2)

This tutorial will describe the logistic function used to model binary classification problems. We will provide derivations of the gradients used for optimizing any parameters with regards to the cross-entropy .

To output discrete classes with neural networks, we can model a probability distribution over the output classes $t$. For the classification of 2 classes $t=1$ or $t=0$ we can use the logistic function used in logistic regression . For multiclass classification there exists an extension of this logistic function called the softmax function , which is used in multinomial logistic regression . The following section will explain the softmax function and how to derive it. What follows here will explain the logistic function and how to optimize it.

This is the first part of a 2-part tutorial on classification models trained by cross-entropy:

In [1]:

## Logistic function

The goal is to predict the target class $t$ from an input $z$. The probability $P(t=1 | z)$ that input $z$ is classified as class $t=1$ is represented by the output $y$ of the logistic function computed as $y = \sigma(z)$. The logistic function $\sigma$ is defined as: $$\sigma(z) = \frac{1}{1+e^{-z}}$$

This logistic function, implemented below as  logistic(z)  , maps the input $z$ to an output between $0$ and $1$ as is illustrated in the figure below.

We can write the probabilities that the class is $t=1$ or $t=0$ given input $z$ as:

$$\begin{split} P(t=1| z) & = \sigma(z) = \frac{1}{1+e^{-z}} \\ P(t=0| z) & = 1 - \sigma(z) = \frac{e^{-z}}{1+e^{-z}} \end{split}$$

Note that input $z$ to the logistic function corresponds to the log odds ratio of $P(t=1|z)$ over $P(t=0|z)$.

$$\begin{split} \log \frac{P(t=1|z)}{P(t=0|z)} & = \log \frac{\frac{1}{1+e^{-z}}}{\frac{e^{-z}}{1+e^{-z}}} = \log \frac{1}{e^{-z}} \\ & = \log(1) - \log(e^{-z}) = z \end{split}$$

This means that the log-odds $\log(P(t=1|z)/P(t=0|z))$ changes linearly with $z$. If $z = x \cdot w$, as in a typical neural network linear layer, then as a result, the log-odds will change linearly with the parameters $w$ and input samples $x$.

In [2]:
def logistic(z):
"""Logistic function."""
return 1 / (1 + np.exp(-z))

In [3]:

### Derivative of the logistic function

Since neural networks typically use gradient based opimization techniques such as gradient descent it is important to define the derivative of the output $y$ of the logistic function with respect to its input $z$. ${\partial y}/{\partial z}$ can be calculated as:

$$\frac{\partial y}{\partial z} = \frac{\partial \sigma(z)}{\partial z} = \frac{\partial \frac{1}{1+e^{-z}}}{\partial z} = \frac{-1}{(1+e^{-z})^2} \cdot e^{-z} \cdot -1 = \frac{1}{1+e^{-z}} \frac{e^{-z}}{1+e^{-z}}$$

And since $1 - \sigma(z)) = 1 - {1}/(1+e^{-z}) = {e^{-z}}/(1+e^{-z})$ this can be rewritten as:

$$\frac{\partial y}{\partial z} = \frac{1}{1+e^{-z}} \frac{e^{-z}}{1+e^{-z}} = \sigma(z) \cdot (1- \sigma(z)) = y (1-y)$$

This derivative is implemented as  logistic_derivative(z)  and is plotted below.

In [4]:
def logistic_derivative(z):
"""Derivative of the logistic function."""
return logistic(z) * (1 - logistic(z))

In [5]:

### Cross-entropy loss function for the logistic function

The output of the model $y = \sigma(z)$ can be interpreted as a probability $y$ that input $z$ belongs to one class $(t=1)$, or probability $1-y$ that $z$ belongs to the other class $(t=0)$ in a two class classification problem. We note this down as: $P(t=1| z) = \sigma(z) = y$.

The neural network model will be optimized by maximizing the likelihood that a given set of parameters $\theta$ of the model can result in a prediction of the correct class of each input sample. The parameters $\theta$ transform each input sample $i$ into an input to the logistic function $z_{i}$. The likelihood maximization can be written as:

$$\underset{\theta}{\text{argmax}}\; \mathcal{L}(\theta|t,z) = \underset{\theta}{\text{argmax}} \prod_{i=1}^{n} \mathcal{L}(\theta|t_i,z_i)$$

The likelihood $\mathcal{L}(\theta|t,z)$ can be rewritten as the joint probability of generating $t$ and $z$ given the parameters $\theta$: $P(t,z|\theta)$. Since $P(A,B) = P(A|B)P(B)$ this can be written as:

$$P(t,z|\theta) = P(t|z,\theta)P(z|\theta)$$

Since we are not interested in the probability of $z$ we can reduce this to: $\mathcal{L}(\theta|t,z) = P(t|z,\theta) = \prod_{i=1}^{n} P(t_i|z_i,\theta)$. Since $t_i$ is a Bernoulli variable , and the probability $P(t| z) = y$ is fixed for a given $\theta$ we can rewrite this as:

$$\begin{split} P(t|z) & = \prod_{i=1}^{n} P(t_i=1|z_i)^{t_i} \cdot (1 - P(t_i=1|z_i))^{1-t_i} \\ & = \prod_{i=1}^{n} y_i^{t_i} \cdot (1 - y_i)^{1-t_i} \end{split}$$

Since the logarithmic function is a monotone increasing function we can optimize the log-likelihood function $\underset{\theta}{\text{argmax}}\; \log \mathcal{L}(\theta|t,z)$. This maximum will be the same as the maximum from the regular likelihood function. The benefit of using the log-likelihood is that it can prevent numerical underflow when the probabilities are low. The log-likelihood function can be written as:

$$\begin{split} \log \mathcal{L}(\theta|t,z) & = \log \prod_{i=1}^{n} y_i^{t_i} \cdot (1 - y_i)^{1-t_i} \\ & = \sum_{i=1}^{n} t_i \log(y_i) + (1-t_i) \log(1 - y_i) \end{split}$$

Minimizing the negative of this function (minimizing the negative log likelihood) corresponds to maximizing the likelihood. This error function $\xi(t,y)$ is typically known as the cross-entropy error function (also known as log-loss):

$$\begin{split} \xi(t,y) & = - \log \mathcal{L}(\theta|t,z) \\ & = - \sum_{i=1}^{n} \left[ t_i \log(y_i) + (1-t_i)\log(1-y_i) \right] \\ & = - \sum_{i=1}^{n} \left[ t_i \log(\sigma(z)) + (1-t_i)\log(1-\sigma(z)) \right] \end{split}$$

This function looks complicated but besides the previous derivation there are a couple of intuitions why this function is used as a loss function for logistic regression. First of all it can be rewritten as:

$$\xi(t_i,y_i) = \begin{cases} -\log(y_i) & \text{if } t_i = 1 \\ -\log(1-y_i) & \text{if } t_i = 0 \end{cases}$$

Which in the case of $t_i=1$ is $0$ if $y_i=1$ $(-\log(1)=0)$ and goes to infinity as $y_i \rightarrow 0$ $(\underset{y \rightarrow 0}{\text{lim}}{(-\log(y))} = +\infty)$. The reverse effect is happening if $t_i=0$.
So what we end up with is a loss function that is $0$ if the probability to predict the correct class is $1$ and goes to infinity as the probability to predict the correct class goes to $0$.

Notice that the loss function $\xi(t,y)$ is equal to the negative log probability that $z$ is classified as its correct class:
$$\begin{split} -\log(P(t=1| z)) &= -\log(y) \\ -\log(P(t=0| z)) &= -\log(1-y) \end{split}$$

By minimizing the negative log probability, we will maximize the log probability. And since $t$ can only be $0$ or $1$, we can write $\xi(t,y)$ as:

$$\xi(t,y) = -t \log(y) - (1-t) \log(1-y)$$

Which will give $\xi(t,y) = - \sum_{i=1}^{n} \left[ t_i \log(y_i) + (1-t_i)\log(1-y_i) \right]$ if we sum over all $n$ samples.

Another reason to use the cross-entropy function is that in simple logistic regression this results in a convex loss function, of which the global minimum will be easy to find. Note that this is not necessarily the case anymore in multilayer neural networks.

#### Derivative of the cross-entropy loss function for the logistic function

The derivative ${\partial \xi}/{\partial y}$ of the loss function with respect to its input can be calculated as:

$$\begin{split} \frac{\partial \xi}{\partial y} &= \frac{\partial (-t \log(y) - (1-t) \log(1-y))}{\partial y} = \frac{\partial (-t \log(y))}{\partial y} + \frac{\partial (- (1-t) \log(1-y))}{\partial y} \\ & = -\frac{t}{y} + \frac{1-t}{1-y} = \frac{y-t}{y(1-y)} \end{split}$$

This derivative will give a nice formula if it is used to calculate the derivative of the loss function with respect to the inputs of the classifier ${\partial \xi}/{\partial z}$ since the derivative of the logistic function is ${\partial y}/{\partial z} = y (1-y)$:

$$\frac{\partial \xi}{\partial z} = \frac{\partial y}{\partial z} \frac{\partial \xi}{\partial y} = y (1-y) \frac{y-t}{y(1-y)} = y-t$$

This was the first part of a 2-part tutorial on classification models trained by cross-entropy:

To see the logistic function in action on a minimal neural network, please read part 2 of this series on how to implement a neural network in NumPy.

In [6]:
Python implementation: CPython
Python version       : 3.9.4
IPython version      : 7.23.1

numpy     : 1.20.2
matplotlib: 3.4.2
seaborn   : 0.11.1



This post at peterroelants.github.io is generated from an IPython notebook file. Link to the full IPython notebook file

Originally published on June 10, 2015.